Self-Confidence and Relationship Status in Supporting Work Readiness through Industrial Counseling - Akhmad Farell; Marsela Dominika Negor; Amelia Yupita; Nor Syifahayati; Karyanti Karyanti; Asep Solikin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: Readiness to enter the workforce in a dynamic industrial era is strongly influenced by individuals' psychological conditions, particularly self-confidence as an aspect of self-efficacy. Aim: This study aims to describe the level of self-confidence, the respondents' social relationship status, and to identify the association between these variables in the context of developing work readiness through industrial guidance and counseling. Method: This study employs a quantitative, descriptive design. Results and Discussion: The research subjects comprised 204 respondents, and data were collected using a closed-ended questionnaire on a categorical scale. Data analysis was conducted using descriptive statistics and cross-tabulation to identify patterns of relationships between variables. The results indicate that the majority of respondents have moderate to high self-confidence, with almost none falling into the low category. The respondents' marital status is predominantly unmarried; however, it does not appear to have a significant influence on self-confidence levels. Conclusion: These findings emphasize that strengthening self-confidence can be a primary focus of industrial counseling interventions to support readiness in facing the work environment. This study recommends expanding the range of variables in future research, including motivation, interpersonal skills, and social support, to achieve a more comprehensive understanding of young people's work readiness.